PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) PADA PEMBELAJARAN PIPS UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SUMBER DAYA ALAM DAN KEGIATAN EKONOMI - Soleh, Maulana Ibnu; Kurnia, Dadang; Sunarya, Dede Tatang (Jurnal Pena Ilmiah, 2017)
The ability of students of Padasukaelementary school 1 grade IV in the material of natural resources and economic activity has not reached the maximum result. This is due to the use of learning models that are less varied so it looks at the results of student learning is still low. To overcome the problems faced by students, the effort that can be done is to choose the media and learning model that is expected to help the students in understanding the material of natural resources and economic activity by using TGT learning model. The purpose of this study is to improve the learning process so that IPS learning outcomes can be improved through cooperative learning type TGT in grade IVA students Padasukaelementary school 1. This type of research is a classroom action research with the design used is a spiral model Kemmis and Mc. Taggart. The instrument used is by observation techniques, interviews, field notes, and test results learning. While for data validation, used member check, triangulation, and expert opinion. The subjects of this study are the students of grade IVA Padasukaelementary school 1 Lesson Year 2016/2017 consisting of 28 students. This study was conducted three cycles, each cycle covering the planning, implementation, observation, and reflection. Based on the results of research actions that have been done, overall has shown an increase both in process and learning outcomes. For the learning cycle I completed 42%, the second cycle reached 75%, and the third cycle reached 96.5%. Thus, it can be concluded that the use of cooperative learning model type TGT can improve student learning outcomes on natural resource materials and economic activities in class IVAPadasuka elementary school 1 North Sumedang, Sumedang District.